2014
DOI: 10.1130/g35751.1
|View full text |Cite
|
Sign up to set email alerts
|

How waves shape salt marshes

Abstract: We present high-resolution field measurements of five sites along the United States Atlantic Coast, and cellular automata simulations, to investigate the erosion of marsh boundaries by wave action. According to our analysis, when salt marshes are exposed to high wave energy conditions their boundaries erode uniformly. The resulting erosion events follow a Gaussian distribution, yielding a relatively smooth shoreline. On the contrary, when wind waves are weak and the local marsh resistance is strong, jagged mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
85
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 26 publications
7
85
3
Order By: Relevance
“…Wave erosion constitutes one of the main contributions to salt marsh deterioration, and even very small waves can cause failure of large salt marsh blocks (2,7,17). Despite the complexity of the problem, some studies have identified a correlation between wave energy and lateral rates of marsh erosion (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wave erosion constitutes one of the main contributions to salt marsh deterioration, and even very small waves can cause failure of large salt marsh blocks (2,7,17). Despite the complexity of the problem, some studies have identified a correlation between wave energy and lateral rates of marsh erosion (18,19).…”
mentioning
confidence: 99%
“…salt marsh | resilience | hurricanes | wind waves | erosion T he potential of salt marshes to serve as natural buffers against violent storms seems even more important in view of significant threats imposed by climate change, such as increased storminess and higher hurricane activity registered in the past decades (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Recent research results show that salt marshes reduce wave energy during storms and possibly, mitigate storm surges (13)(14)(15).…”
mentioning
confidence: 99%
“…The marshes in Shell Bay display jagged outlines, indicative of low wave and tidal current stress (Leonardi and Fagherazzi, 2014). The Stour Estuary marshes (S2) 6 km upstream of the mesotidal Stour mouth are subject to a spring tidal range of 3.8 m and fluviotidal currents due to their estuarine fringing position (sensu Allen, 2000) and therefore display more linear boundaries.…”
Section: Test Sitesmentioning
confidence: 99%
“…However, many natural forces are also erosive, including waves formed by winds over long stretches of water (Pye 1995;Schwimmer 2001;Leonardi et al 2016), but these waves can be larger when water becomes deepened by sealevel rise, excessive dredging, or other reasons. Tidal currents can induce meander patterns of erosion and redeposition (Biggs 1982;Kearney et al 1988;Kleinhans et al 2009) and wind-driven wave action can also have strong effects (Fagherazzi and Wiberg 2008;Leonardi and Fagherazzi 2014;Priestas et al 2015). The interaction of sea-level rise and sediment deposition rates can also cause the widening of creeks (Fagherazzi et al 2012).…”
Section: Communicated By Carles Ibanez Martimentioning
confidence: 99%